Soft rot in organic banana pseudostem (Musa sp): Symptomatology, cultural and biochemical characterization, pathogenicity, and management alternatives - Aguilar-Anccota, René (2021)
The banana (Musa sp.) is a very important crop in the socioeconomic development of Peru. The soft rot disease has been causing economic losses. The objective was to isolate and identify the causal agent of soft rot in banana and to implement management alternatives. Bacteria were isolated from pseudostem with soft rot symptoms from 11 producing areas in the Chira Valley. The pathogenicity tests were carried on pseudostem segments and banana shoots. The eight isolates were culturally, morphologically and biochemically characterized: All isolates were Gram negative, rod-shaped, with peritrichous flagella and colonies formed deep cavities on crystal violet pectate (CVP) medium. Biochemical tests showed a positive catalase reaction, gelatin hydrolysis, glucose and lactose fermentation, and tolerance to NaCl 5%. However, on TSI (Triple Iron Sugar) medium and erythromycin sensitivity only isolates A2M, A3Ma, A5Mall, A7VF, A9Sa and A10 reacted positively and isolates A6Q and A11Sal negatively. Growth at 28, 30, 36, 36, 37 and 45 °C was positive for all eight isolates, with the exception A6Q and A11Sal which did not develop at 45 °C. Cultural characteristics, biochemical and pathogenicity tests allowed to identify six isolates as Pectobacterium chrysanthemi and two as P. carotovorum subsp. carotovorum. Disease management is based on the use of certified suckers, adequate fertilization, organic matter applications, biocontrol agents and weevil insect control.